Professionally Relevant Traits of the Heads of Correctional Facilities - Karpova, G.S.; Cheremisova, I.V.; Kovalchuk, I.A. (Psihologiâ i pravo, 2021)
The article is dedicated to the study of professionally relevant personality traits, abilities and orientations of the officials of correctional facilities, holding senior positions in comparison to those of their subordinates. The traits are an integral part of the psychological and educational component of their professional competence. They reflect the most general, invariant psychological characteristics which ensure the success in their professional performance irregardless of their function or position. The hypothesis was that officials holding senior positions possess the professionally relevant traits to a greater degree, than their subordinates do. The processing of the obtained data demonstrated that senior officers surpass their subordinates in a number of professionally relevant traits (communicative, intellectual, emotional and volitional qualities). This qualities can be viewed as the psychological foundation for the formation of the subject position in professional development. The results are integrated into prospective studies of the factors and conditions for professional and personal development of penitentiary personnel. They are also used in designing programs for fostering their professional competence. Статья посвящена изучению профессионально важных качеств, способностей и ориентаций сотрудников исправительных учреждений (ИУ), состоящих на руководящих должностях, в сравнении с сотрудниками-подчиненными. Рассматриваемые качества являются элементами психолого-педагогического компонента их профессиональной компетентности. Они отражают общие, инвариантные психологические характеристики, которые обеспечивают успешность в профессиональной деятельности независимо от функциональной направленности и должности. Гипотеза заключалась в том, что у сотрудников-руководителей профессионально важные качества выражены в большей степени, чем у сотрудников-подчиненных. Математическая обработка данных показала, что руководители превосходят сотрудников-подчиненных по ряду качеств (коммуникативных, интеллектуальных, эмоционально-волевых и др.), которые выступают психологическим основанием для формирования субъектной позиции в профессиональном развитии. Полученные результаты учитываются в исследованиях факторов и условий профессионально-личностного роста сотрудников ИУ, при разработке программ, направленных на развитие их профессиональной компетентности.